Efektifitas Penentuan Skala Nyeri dengan Menggunakan Aplikasi Berbasis Android terhadap Pengkajian Asuhan Keperawatan pada Mahasiswa Praktik Klinik Keperawatan - Nasir, Andi; Purnomo, Edi; Supratti, Supratti (Jurnal Gema Keperawatan, 2023)
One of the basic things in assessing nursing care for patients is the pain caused by the disease they suffer from. Pain is a common reason for someone to seek medical care. Someone experiencing pain will feel depressed so that person looks for ways to relieve the pain. Pain is an unpleasant sensory and emotional experience resulting from actual or potential tissue damage. Pain assessment can be done by carrying out verbal (subjective) and nonverbal (objective) assessments. This research aims to identify the pain scale in patients by determining the pain scale during nursing care assessments using an Android-based application. Research design with pre-experiment pretest and posttest design using One Shot Case Study. The results of the dependent t test analysis showed that the t value was -13.31 ttable 1.672 with a p-value of 0.001 0.05, indicating that assessing the pain scale using an Android-based application was effective in improving students' clinical practice abilities. With a correlation of 0.703, this means that there is a positive and significant relationship with the treatment or application treatment using an Android cellphone which is effective in determining the pain scale in clinical practice students at the Mamuju Regency Hospital.